JEJAK DIASPORA DAN NARASI KEHIDUPAN PICTURE BRIDES DALAM NOVEL THE BUDDHA IN THE ATTIC KARYA JULIE OTSUKA - Sindhy Sintya Mianani (Literary Studies, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2019)
Amerika Serikat yang dikenal sebagai negeri para imigran telah menarik jutaan imigran yang bermimpi untuk memiliki masa depan cerah ke pesisir negaranya. Sebagai negeri para imigran, pengalaman diaspora para imigran di Amerika sejatinya merupakan topik yang telah banyak dieksplorasi dalam dunia kesusastraan. Akan tetapi, sedikit sekali yang berbicara mengenai diaspora warga Jepang di Amerika. Sebagai sebuah awalan, studi ini menguraikan pengalaman diaspora para perempuan Jepang yang mengadu nasib di daratan Amerika sebagai picture brides dalam novel The Buddha in the Attic karya Julie Otsuka. Tidak hanya berbicara mengenai kehidupan picture brides di Amerika, The Buddha in the Attic juga menceritakan pengalaman imigran Jepang pada masa Perang Dunia II yang berujung pada kamp-kamp konsentrasi. Untuk menguraikan permasalahan tersebut, studi ini menerapkan teori Historical Poetics yang diprakarsai oleh Alan Swingewood untuk memperoleh hasil analisis yang rigid. Dikemas dengan subjek orang pertama jamak (first person plural), Julie Otsuka menciptakan sebuah narasi tentang kehidupan para picture brides dan imigran Jepang secara kolektif. Tindakan yang dilakukan sang penulis ini, disinyalir sebagai bentuk post-memory-nya sebagai generasi ketiga imigran Jepang (sansei) di Amerika. Kata kunci: diaspora, narasi, historical poetics, picture brides, post-memory United States of America which is acknowledged as the land of immigrants has lured millions of those who seek for a bright future to its coast. As the land of immigrants, diaporic phenomenon in America has been explored extensively in literary world. However, a very few number has yet to conduct a study on Japanese diasporic phenomenon in America. To begin with, this study attempts to describe the diaporic phenomenon of Japanese women who came to America as picture brides in Julie Otsuka’s The Buddha in the Attic. Not only narrating the the story of picture brides in America, The Buddha in the Attic also tells the story of Japanese migrants who ended up in concentracion camps during the Word War II period. To solve the problem aforementioned, this study applies Alan Swingewood’s Historical Poetics to get adequate results. As the novel is written in first person plural prounoun, Julie Otsuka is said to create narratives on Japanese picture brides and Japanese migrants collectively. What the author does is assumed as the post-memory of being the third generation of Japanese migrants (sansei) in America. Keywords: diaspora, narratives, historical poetics, picture brides, post-memory